Synthesis of CHA zeolitic materials, CHA zeolitic materials obtainable therefrom and SCR catalysts comprising same

By using a linear diquaternary ammonium salt organic structure directing agent and a specific proportion of X2O3 and YO2 to prepare CHA-type skeleton structure zeolite, the problem of insufficient preparation methods in the existing technology is solved, and the performance of NOx selective catalytic reduction at high temperature is improved.

CN120813545APending Publication Date: 2025-10-17BASF MOBILE EMISSION CATALYST GMBH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480015382.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-02-28
Filing Date
2024-02-27
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

The existing technology lacks an effective method to prepare zeolite materials with a CHA-type framework structure, and in particular, the catalytic performance for selective catalytic reduction of NOx needs to be improved.

Method used

A linear diquaternary ammonium salt organic structure directing agent (OSDA) is used to prepare CHA-type framework zeolite in zeolite synthesis. Combined with a specific ratio of X2O3 and YO2 sources, a zeolite with a CHA-type framework structure is formed after crystallization treatment, which can be further combined with a promoter metal.

Benefits of technology

The prepared CHA-type framework structure zeolite exhibits excellent stability and improved NOx selective catalytic reduction performance at high temperatures, significantly improving the NOx conversion rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005569545800000201
    Figure BDA0005569545800000201
  • Figure BDA0005569545800000211
    Figure BDA0005569545800000211
  • Figure HDA0005569545810000011
    Figure HDA0005569545810000011
Patent Text Reader

Abstract

The present invention relates to a process for preparing a zeolite having a CHA-type framework structure comprising X2O3 and YO2 wherein X is a trivalent element and Y is a tetravalent element, comprising (1) preparing a synthesis mixture comprising: (A) a source of X2O3, (B) a source of YO2, and (C) a source of organic structure directing agent (OSDA), the source comprises a biquaternary ammonium cation of formula (I) or a combination of biquaternary ammonium cations of formula (R1R2R3) N + (CH2) nN + (R4R5R6) (I) as defined in the claims, and (2) subjecting the synthesis mixture to crystallization conditions to form a zeolite having a CHA-type framework structure. The invention also relates to the zeolite having a CHA-type framework structure obtained by the method and to the use of the zeolite in a catalyst for the selective catalytic reduction of nitrogen oxides.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present invention relates to a process for the synthesis of a zeolitic material having a CHA type framework structure, a zeolitic material obtainable therefrom and an SCR catalyst comprising the same. BACKGROUND

[0002] Catalytic articles are indispensable for modern internal combustion engines to treat the exhaust gas before it is emitted into the air. Exhaust gas from internal combustion engines usually contains particulate matter (PM), nitrogen oxides (NOx) such as NO and / or NO2, unburned hydrocarbons (HC) and carbon monoxide (CO). Since NOx has an environmental negative impact on ecosystems, animal and plant life, the control of NOx emissions has been one of the most important topics in the automotive field.

[0003] One of the effective techniques for the removal of NOx from internal combustion engine exhaust gas is the selective catalytic reduction (SCR) of NOx with ammonia or a second source of ammonia. Recently, small-pore zeolites for the selective catalytic reduction of NOx have been proposed, wherein CHA type zeolites have been extensively studied and found to be one of the most promising SCR catalysts, especially when the zeolite is exchanged with a metal promoter such as Cu or Fe.

[0004] Chabazite is a class of naturally occurring zeolites and also has a synthetic CHA form. One well-known synthetic CHA type zeolite is a crystalline CHA material designated SSZ-13, as reported in US 4,544,538. SSZ-13 is prepared under crystallization conditions using a structure directing agent comprising N-alkyl-3-quinuclidinol cations, N,N,N-trialkyl-1-adamantammonium cations, N,N,N-trialkyl-2- exoaminonorbornane cations, or mixtures thereof. The synthesis of CHA type zeolites using other structure directing agents has also been developed, as reported, for example, in the following non-patent and patent literature.

[0005] Itakura Masaya et al. in Chemistry Letters, 2008, Vol. 37, No. 9, pages 908 to 909 describe a process for the synthesis of CHA utilizing benzyltrimethylammonium hydroxide as structure directing agent.

[0006] US 2010 / 254895 A1 discloses a process for preparing a CHA type zeolite using a cationic 1,4-diazoniabicyclo[2.2.2]octane based structure directing agent in combination with at least one cationic cyclic nitrogen-containing structure directing agent.

[0007] WO 2020 / 039074 A1 discloses a process for preparing a CHA type zeolite using a structure directing agent comprising a compound having the formula [NR 1 R 2 R 3 R4 ] of the formula (I) wherein R 1 , R 2 , R 3 and R4 are independently a C1-C4-alkyl group optionally substituted by one or more hydroxyl groups.

[0008] Biaohua Chen et al. in Environmental Science & Technology, 2014, 48, pages 13909 to 13916 describe a method for synthesizing SSZ-13 using choline chloride as a structure directing agent.

[0009] WO 2013 / 035054 A1 discloses a process for preparing a zeolitic material having a CHA-type framework structure, wherein the process employs an N,N-dimethylammonium organic template comprising N,N-dimethylpiperidinium.

[0010] There is still a need for further processes for preparing a zeolitic material having a CHA-type framework structure, in particular processes which are capable of providing a CHA-type zeolitic material having improved catalytic performance for the selective catalytic reduction of NOx. SUMMARY

[0011] It is an object of the present invention to provide a new process for preparing a zeolitic material having a CHA-type framework structure. It is a further object of the present invention to provide a SCR catalyst based on a zeolite having a CHA-type framework structure having improved catalytic performance for the selective catalytic reduction of NOx.

[0012] These objects are achieved by using a linear diquat organic structure directing agent (OSDA) in the synthesis of the zeolite. It has surprisingly been found that a zeolite having a CHA-type framework structure prepared with a linear diquat organic structure directing agent has the desired activity, in particular in combination with an excellent stability against aging at high temperatures, e.g. at 800 °C or higher.

[0013] Thus, in a first aspect, the present invention relates to a process for preparing a zeolitic material having a CHA-type framework structure, the framework structure comprising X2O3 and YO2, wherein X is a trivalent element and Y is a tetravalent element, the process comprising

[0014] (1) preparing a synthesis mixture, the synthesis mixture comprising

[0015] (A) a source of X2O3,

[0016] (B) a source of YO2, and

[0017] (C) a source of organic structure directing agents (OSDA) comprising a bis-quaternary ammonium cation of formula (I) or a combination of bis-quaternary ammonium cations of formula (I),

[0018] (R1R2R3)N + (CH2) n N + (R4R5R6)(I)

[0019] wherein

[0020] R1, R2, R3, R4, R5 and R6 are independently of each other selected from the group consisting of C1-C 10 alkyl, and n is an integer in the range of 3 to 10,

[0021] or

[0022] wherein

[0023] one of R1, R2 and R3 is selected from the group consisting of C1-C 10 alkyl, and the other two are linked together to form a C4-C6 alkylene group,

[0024] one of R4, R5 and R6 is selected from the group consisting of C1-C 10 alkyl, and the other two are linked together to form a C4-C6 alkylene group, and

[0025] n is an integer in the range of 3 to 10; and

[0026] (2) subjecting the synthesis mixture to crystallization conditions to form a CHA-type framework structure.

[0027] In a second aspect, the present application relates to a zeolite having a CHA-type framework structure, obtained and / or obtainable by a process as described herein.

[0028] In a third aspect, the present application relates to a metal-promoted zeolite having a CHA-type framework structure, comprising a zeolite obtained and / or obtainable by a process as described herein and a promoter metal.

[0029] In a fourth aspect, the present application relates to the use of a zeolite having a CHA-type framework structure according to the second aspect or a metal-promoted zeolite according to the third aspect in a catalyst for selective catalytic reduction (SCR) of NOx.

[0030] In a fifth aspect, the present application relates to a catalytic article in the form of an extrudate comprising an SCR catalyst composition or in the form of a monolith comprising a washcoat containing an SCR catalyst composition on a substrate, wherein the SCR catalyst composition comprises a metal-promoted zeolite having a CHA-type framework structure as described herein.

[0031] In a sixth aspect, the present application is directed to an exhaust gas treatment system comprising an internal combustion engine and an exhaust gas conduit in fluid communication with the internal combustion engine, wherein a catalytic article as described herein is present in the exhaust gas conduit. BRIEF DESCRIPTION OF DRAWINGS

[0032] Figure 1A 、 Figure 1B and Figure 1C SEM images of the zeolites (zeolites A, B and C) from Examples 2, 3 and 4, respectively, are shown.

[0033] Figure 2 XRD patterns of the zeolites (zeolites A, B and C) from Examples 2, 3 and 4, respectively, are shown. DETAILED DESCRIPTION

[0034] The present application is described in detail below. It should be appreciated that the present application can be embodied in many different forms and should not be construed as limited to the embodiments set forth herein.

[0035] In this document, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. The terms "comprises," "comprising," "includes," "including," and the like can be used interchangeably with "containing" or "containing" and are each

[0036] As used herein, the terms "zeolite having a CHA-type framework structure," "CHA-type zeolite," "CHA zeolite," and the like are intended to mean a molecular sieve material that exhibits an XRD pattern of a CHA-type framework structure and will be used interchangeably with one another hereinafter. These terms are also intended to include any form of the zeolite, such as as-synthesized form, calcined form, NH4-exchanged form, H form, and metal-substituted form.

[0037] As used herein, the term "as-synthesized" is intended to mean the form of the zeolite after crystallization and drying, prior to removal of the organic structure directing agent.

[0038] As used herein, the term "calcined form" is intended to mean the form of the zeolite after calcination.

[0039] In a first aspect, the present application provides a method for preparing a zeolite having a CHA-type framework structure, the framework structure comprising X2O3 and YO2, wherein X is a trivalent element and Y is a tetravalent element, the method comprising

[0040] (1) preparing a synthesis mixture, the synthesis mixture comprising

[0041] (A) a source of X2O3,

[0042] (B) a source of YO2, and

[0043] (C) a source of an organic structure directing agent (OSDA), the source comprising a bis-quaternary ammonium cation of formula (I) or a combination of bis-quaternary ammonium cations of formula (I),

[0044] (R1R2R3)N + (CH2) n N + (R4R5R6)(I)

[0045] wherein

[0046] R1, R2, R3, R4, R5, and R6 are each independently selected from the group consisting of C1-C 10 alkyl, and n is an integer in the range of 3 to 10,

[0047] or

[0048] wherein

[0049] one of R1, R2, and R3 is selected from the group consisting of C1-C 10 alkyl, and the other two are linked together to form a C4-C6 alkylene group,

[0050] one of R4, R5, and R6 is selected from the group consisting of C1-C 10 alkyl, and the other two are linked together to form a C4-C6 alkylene group, and

[0051] n is an integer in the range of 3 to 10; and

[0052] (2) subjecting the synthesis mixture to crystallization conditions to form a zeolite having a CHA-type framework structure.

[0053] The synthesis mixture provided in step (1) comprises a source of X2O3, wherein X is a trivalent framework element, and a source of YO2, wherein Y is a tetravalent framework element. X can be any conventional trivalent framework element. Preferably, X is selected from the group consisting of Al, B, In, Ga, and any combination thereof, with Al being more preferred. Additionally, Y can be any conventional tetravalent framework element. Preferably, Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and any combination thereof, with Si being more preferred. In particular, X is Al and Y is Si.

[0054] Suitable sources of X2O3 can be any known material that can be used to provide a trivalent framework element during zeolite synthesis. In some embodiments where X is Al, suitable examples of sources of AI2O3 can include, but are not limited to, alumina, aluminum hydroxide, aluminate, aluminates, aluminum salts, FAU zeolites, LTA zeolites, LTL zeolites, BEA zeolites, MFI zeolites, and any combination thereof, more preferably alumina, aluminates, aluminum salts, FAU zeolites, and any combination thereof. In particular, the source of AI2O3 can be selected from the group consisting of alumina, AIO(OH), AI(OH)3, tri(Ci-C5)aluminates, aluminum halides, aluminum sulfate, aluminum phosphate, aluminum fluorosilicate, FAU zeolites, and any combination thereof. For example, the FAU zeolite can be selected from the group consisting of faujasite, [Al-Ge-O]-FAU, [Al-Ge-O]-FAU, [Ga-Al-Si-O]-FAU, [Ga-Ge-O]-FAU, [Ga-Si-O]-FAU, CSZ-1, US-Y, ECR-30, LZ-210, Li-LSX, SAPO-37, ZSM-20, ZSM-3, zeolite X, and zeolite Y, more preferably from the group consisting of faujasite, zeolite X, zeolite Y, US-Y, and LZ-210. Zeolite Y can be particularly mentioned as a source of X2O3.

[0055] Suitable sources of YO2 can be any known material that can be used to provide a tetravalent framework element during zeolite synthesis. In some embodiments where Y is Si, suitable sources of YO2 can include, but are not limited to, fumed silica, precipitated silica, silica hydrosol, silica gel, colloidal silica, silicic acid, silicates, alkali metal silicates, hydrated sodium metasilicate, hemisilicates, disilicates, silicates, FAU zeolites, LTA zeolites, LTL zeolites, BEA zeolites, MFI zeolites, and any combination thereof. In particular, the source of YO2 can be selected from the group consisting of fumed silica, sodium silicate, potassium silicate, FAU zeolites, and any combination thereof, more preferably fumed silica, FAU zeolites, and any combination thereof. For example, the FAU zeolite can be selected from the group consisting of faujasite, [Al-Ge-O]-FAU, [Al-Ge-O]-FAU, [Ga-Al-Si-O]-FAU, [Ga-Ge-O]-FAU, [Ga-Si-O]-FAU, CSZ-1, US-Y, ECR-30, LZ-210, Li-LSX, SAPO-37, ZSM-20, ZSM-3, zeolite X, and zeolite Y, more preferably from the group consisting of faujasite, zeolite X, zeolite Y, US-Y, and LZ-210. In particular, one or more materials selected from the group consisting of fumed silica, precipitated silica, silica hydrosol, silica gel, colloidal silica, and zeolite Y can be mentioned as a source of YO2.

[0056] It will be appreciated that the source of X2O3 and the source of YO2 can be provided separately (i.e. separate sources) and / or jointly (i.e. a combined source). In the latter case, the source can be provided by, for example, a zeolite containing the framework elements X and Y. It is envisaged that the synthesis mixture provided in step (1) can comprise a combined source of X2O3 and YO2 as well as one or more additional separate sources of X2O3 and YO2.

[0057] In some particular embodiments, the synthesis mixture provided in step (1) comprises a source of Al2O3 and a source of SiO2 in the form of a separate source or a combined source. Thus, an aluminosilicate zeolite having a CHA-type framework structure will be obtained from the process according to the present application.

[0058] The term "aluminosilicate" as used in the context of zeolites is intended to mean a framework consisting primarily of aluminum oxide and silicon dioxide, which can or can not contain framework elements other than oxygen, aluminum and silicon.

[0059] In certain illustrative embodiments, the synthesis mixture provided in step (1) comprises a FAU zeolite as a combined source of Al2O3 and SiO2 as well as an additional source of SiO2. In particular, the FAU zeolite is zeolite Y, which can be Na + form, H form or NH4 + exchanged form. More preferably, the zeolite Y has a molar ratio of SiO2 to Al2O3 of not more than 40 or not more than 30. The additional source of SiO2 is selected from the group consisting of fumed silica, precipitated silica, silica hydrosol, silica gel and colloidal silica, including mixtures of two or more thereof.

[0060] The synthesis mixture provided in step (1) has a YO2:X2O3 molar ratio in the range of 5 to 100, for example 10 to 60 or 15 to 30.

[0061] A suitable source of organic structure directing agent (OSDA) can be a compound containing a bis-quaternary ammonium cation of formula (I) as described herein, in particular a compound containing a bis-quaternary ammonium cation of formula (I), wherein R1, R2, R3, R4, R5 and R6 are independently of each other selected from C1-C6 alkyl, and n is an integer in the range of 3 to 10.

[0062] Preferably, the source of organic structure directing agent is selected from a compound containing a bis-quaternary ammonium cation of formula (I)

[0063] (R1R2R3)N + (CH2) n N + (R4R5R6)(I)

[0064] wherein

[0065] R1, R2, R3, R4, R5, and R6 are the same and selected from C1-C6 alkyl, and

[0066] n is 4 to 7, or

[0067] combinations thereof.

[0068] More preferably, the source of organic structure directing agent is selected from a compound containing a bis-quaternary ammonium cation of formula (I), wherein each of R1, R2, R3, R4, R5, and R6 is a methyl, ethyl, or propyl group, preferably an ethyl group, and n is 5, 6, or 7, or combinations thereof.

[0069] Most preferably, the source of organic structure directing agent is selected from a compound containing a bis-quaternary ammonium cation of formula (la)

[0070] (C2H5)3N + (CH2) n N + (C2H5)3 (la)

[0071] wherein

[0072] n is 5, 6, or 7, or

[0073] combinations thereof.

[0074] In some particular embodiments, the organic structure directing agent comprises N,N,N,N',N',N'-hexaethyl-1,5-pentanediammonium (Et6-diquat-5), i.e. a bis-quaternary ammonium cation of formula (I), wherein each of R1, R2, R3, R4, R5, and R6 is an ethyl group and n is 5, or a bis-quaternary ammonium cation of formula (la), wherein n is 5.

[0075] Suitable compounds comprising a bis-quaternary ammonium cation of formula (I) or (la) can be in the form of a salt. The counterion, i.e. the anion of the salt, is not particularly limited and can be a halide such as fluoride, chloride, and bromide, a hydroxide, a sulfate, a nitrate, a carboxylate such as acetate, and any combination thereof. In particular, the anion can be selected from the group consisting of chloride, bromide, hydroxide, sulfate, or any combination thereof. Preferably, the compound comprising a bis-quaternary ammonium cation is a hydroxide, chloride, or bromide, in particular a hydroxide of a bis-quaternary ammonium cation of formula (I) or (la) as described hereinabove.

[0076] According to the present invention, the organic structure directing agent (OSDA) may or may not contain cations other than the diquaternary ammonium cations of formula (I) or (Ia) as described herein. In some specific embodiments, the organic structure directing agent (OSDA) and therefore the synthesis mixture provided in step (1) do not contain cations of OSDA other than the diquaternary ammonium cations of formula (I) or (Ia) as described herein.

[0077] Preferably, the synthesis mixture provided in step (1) has a molar ratio of diquaternary ammonium cation (Q) to YO2 source calculated as YO2 (Q:YO2) in the range of 0.01 to 1.0, such as 0.05 to 0.5 or 0.08 to 0.2.

[0078] The synthesis mixture provided in step (1) may also include a source of alkali metal and / or alkaline earth metal cations (AM), preferably alkali metal cations. Alkali metals are preferably selected from the group consisting of: Li, Na, K, Cs and any combination thereof, more preferably Na and / or K, and most preferably Na. Alkaline earth metals are preferably selected from the group consisting of: Mg, Ca, Sr and Ba and any combination thereof. Suitable sources of alkali metal and / or alkaline earth metal cations (AM) are typically halides (such as fluorides, chlorides and bromides), hydroxides, sulfates, nitrates and carboxylates (such as acetates) of alkali metal and / or alkaline earth metals, or any combination thereof. Preferably, the source of alkali metal and / or alkaline earth metal cations (AM) comprises chlorides, bromides, hydroxides or sulfates or any combination thereof of alkali metal and / or alkaline earth metals. More preferably, alkali metal hydroxides are used in the synthesis mixture.

[0079] The alkali metal and / or alkaline earth metal cations (AM) may be present in the synthesis mixture relative to the YO2 source in a molar ratio calculated as AM to YO2 in the range of 0.01 to 1.0, eg, 0.03 to 0.5 or 0.05 to 0.3.

[0080] The synthesis mixture provided in step (1) may also contain anions OH - Source. OH - Available sources of can be, for example, metal hydroxides such as alkali metal hydroxides, quaternary ammonium hydroxides. Preferably, the anion OH - It may be derived from one or more of a source of alkali metal and / or alkaline earth metal cations (AM) and a source of organic structure directing agents.

[0081] OH - The anion may be present in an amount of OH in the range of 0.1 to 2.0, such as 0.1 to 1.0 or 0.2 to 0.5 relative to the YO2 source. - The molar ratio calculated for YO2 is present in the synthesis mixture.

[0082] The synthesis mixture provided in step (1) can further comprise at least one solvent, preferably water, more preferably deionized water. The solvent can be comprised in one or more of the starting materials of the synthesis mixture, such as the source of X2O3, YO2 and the organic structure directing agent, and thus be carried into the synthesis mixture, and / or can be introduced separately into the synthesis mixture.

[0083] In some embodiments, the synthesis mixture has a molar ratio of water to YO2 source, calculated as H2O to YO2, in the range of 3 to 100, for example 10 to 80 or 10 to 40.

[0084] In some example embodiments, the synthesis mixture provided in step (1) has a molar composition as shown in Table 1 below.

[0085] Table 1

[0086] Ingredient ratio 1) ]] broad narrow narrower YO2 / X2O3 5 to 100 15 to 60 15 to 30 Q / YO2 0.01 to 1.0 0.05 to 0.5 0.08 to 0.2 AM / YO2 0.01 to 1.0 0.03 to 0.5 0.05 to 0.3 OH - / YO2]] 0.1 to 2.0 0.1 to 1.0 0.2 to 0.5 [H2O / YO2] 3 to 100 10 to 80 10 to 40

[0087] 1) The amount of X2O3 source and YO2 source is calculated as the corresponding oxide

[0088] In some embodiments, the synthesis mixture provided in step (1) can further comprise an amount of CHA zeolite seeds. The seeds of CHA zeolite can be obtained from the process described herein or any other known process without the use of seeds.

[0089] In step (2), the synthesis mixture can be subjected to crystallization conditions to form a zeolite having a CHA-type framework structure without particular limitation. The crystallization can be carried out at an elevated temperature of 80 °C to 250 °C, more preferably 100 °C to 200 °C, for a time sufficient for crystallization, for example 0.5 days to 12 days, or 1 day to 6 days. Typically, the crystallization is carried out under autogenous pressure, for example in a pressure tight vessel such as an autoclave. Furthermore, the crystallization can be carried out with or without stirring.

[0090] The CHA zeolite formed by crystallization can be subjected to a work-up procedure, including for example separation by filtration, optionally washing and drying, to obtain the as-synthesized CHA zeolite. Thus, step (2) in the process according to the present application optionally further comprises a work-up procedure.

[0091] The organic structure directing agent, if any, remaining in the filtrate from the filtration and, optionally, in the washing liquid from the washing, can be recycled and used for further synthesis of CHA zeolite.

[0092] The as-synthesized CHA zeolite typically comprises the bis-quaternary ammonium cations as described above within its structural pores and / or channels.

[0093] In some embodiments, the as-synthesized CHA zeolite from step (2) can be subjected to a calcination procedure. Accordingly, the method according to the present application further comprises a step (3) of calcining the as-synthesized CHA zeolite.

[0094] In some embodiments, the as-synthesized or calcined CHA zeolite can undergo an ion exchange procedure, such that one or more of the ion non-framework elements comprised in the zeolite are exchanged for H + and / or NH4 + Accordingly, the method according to the present application further comprises (4) exchanging one or more of the ion non-framework elements comprised in the zeolite obtained in step (2) or (3) for H + and / or NH4 + , preferably NH4 + .

[0095] Typically, the zeolite which has been exchanged for H + and / or NH4 + in step (4) can be subjected to a work-up procedure comprising, for example, separation, optionally washing and drying, by filtration and / or to a calcination procedure. Accordingly, step (4) in the method according to the present application optionally further comprises a work-up procedure and / or a calcination procedure.

[0096] The calcination in step (3) and / or step (4) can be carried out at a temperature in the range of 300 °C to 900 °C, for example 350 °C to 700 °C, or 400 °C to 650 °C. In particular, the calcination can be carried out in a gas atmosphere having a temperature in the above-mentioned ranges, which can be air, oxygen, nitrogen or a mixture of two or more thereof. Preferably, the calcination is carried out for a period in the range of 0.5 hours to 10 hours, for example 3 hours to 7 hours, or 4 hours to 6 hours.

[0097] The zeolite having a CHA-type framework structure can be successfully obtained from the method described in the first aspect as determined by X-ray powder diffraction (XRD) analysis.

[0098] Accordingly, in a second aspect, the present application provides a zeolite having a CHA-type framework structure obtainable by and / or obtained from the method as described in the first aspect.

[0099] The zeolite having a CHA-type framework structure has a YO2 (e.g. silica) to X2O3 (e.g. alumina) YO2:X2O3 molar ratio (SAR) of 2 or more, wherein the molar ratio is preferably in the range of 4 to 200, more preferably 6 to 100, more preferably 8 to 50, more preferably 10 to 35, more preferably 15 to 30, most preferably 18 to 25. According to the present application, the YO2:X2O3 molar ratio preferably refers to the zeolite having a CHA-type framework structure in its calcined form, more preferably in its calcined H form.

[0100] The zeolite having a CHA-type framework structure according to the present application typically has an average crystal size of at least 200 nm, for example in the range of 0.2 pm to 6 pm. The average crystal size can be determined by scanning electron microscopy (SEM). In particular, the average crystal size is determined via SEM by measuring the crystal size of at least 30 different crystals randomly selected from multiple images covering different areas of the sample.

[0101] It has surprisingly been found that the zeolite having a CHA-type framework structure according to the present application has a crystal morphology with a mosaic pattern texture of the crystal surface, as observed via SEM. In this context, the mosaic pattern is used to describe the surface morphology of the crystals of the zeolite having a CHA-type framework structure, which is intended to refer to a surface pattern made of irregularly shaped patches with irregularly shaped gaps in between.

[0102] The zeolite having a CHA-type framework structure according to the present application is preferably at least 90% phase pure, i.e. at least 90% of the zeolite framework is of the CHA type, as determined by X-ray powder diffraction (XRD) analysis. More preferably, the zeolite having a CHA-type framework structure is at least 95% phase pure, or even more preferably at least 98% or at least about 99% phase pure. Correspondingly, the zeolite having a CHA-type framework structure can contain small amounts (e.g. less than 10%, preferably less than 5%, even more preferably less than 2% or less than 1%) of some other framework as a co-crystal.

[0103] It has surprisingly been found that the zeolite having a CHA-type framework structure obtained from the process described in the first aspect exhibits a significantly higher stability towards aging at temperatures of 800 °C or higher in selective catalytic reduction (SCR) applications of NOx compared to catalysts comprising a zeolite having the same framework type but prepared in other ways.

[0104] Accordingly, in a third aspect, the present application further provides a metal-promoted zeolite having a CHA-type framework structure comprising a zeolite obtained by and / or obtainable by the process according to the present application and a promoter metal.

[0105] As used herein, the term "promoter" refers to a molecule capable of improving the catalytic activity of a zeolite. The term "promoter" is intended to mean a molecule that is not involved in the construction of the zeolite framework structure. The promoter can be present within the zeolite and / or on at least a portion of the zeolite surface.

[0106] In the present context, the promoter is particularly present within a zeolite having a CHA-type framework structure and / or on at least a portion of the surface thereof.

[0107] The zeolite having a CHA-type framework structure is a zeolite obtained by and / or obtainable by the method described in the first aspect and / or as described in the second aspect. Any general and specific description regarding the method in the first aspect or the zeolite having a CHA-type framework structure in the second aspect is hereby incorporated by reference.

[0108] The promoter metal can be any metal known to improve the catalytic performance of a zeolite in selective catalytic reduction (SCR) applications of NOx. Typically, the promoter metal can be selected from the group consisting of transition metals, such as noble metals (such as Au, Ag and platinum group metals), base metals (such as Cr, Zr, Nb, Mo, Fe, Mn, W, V, Ti, Co, Ni, Cu and Zn), alkaline earth metals (such as Ca and Mg) and Sb, Sn and Bi, and any combination thereof.

[0109] In some embodiments, the metal-promoted zeolite having a CHA-type framework structure comprises Cu and / or Fe as promoter metal. In some particular embodiments, the metal-promoted zeolite comprises Cu as promoter metal.

[0110] The promoter metal can be present in the metal-promoted zeolite having a CHA-type framework structure in an amount of 0.1 wt.% to 10 wt.%, preferably 0.5 wt.% to 10 wt.% based on the total weight of the promoter metal and the zeolite having a CHA-type framework structure on an oxide basis. In some particular embodiments, wherein copper, iron or a combination thereof is used as promoter metal, the promoter metal is preferably present in the metal-promoted zeolite having a CHA-type framework structure in an amount of 1 wt.% to 8 wt.%, more preferably 2 wt.% to 6 wt.% based on the total weight of the promoter metal and the zeolite having a CHA-type framework structure on an oxide basis.

[0111] Alternatively, the promoter metal can be present in the metal-promoted zeolite having a CHA-type framework structure in an amount ranging from 0.01 to 2 moles, such as from 0.03 to 1.8 moles, from 0.05 to 1.5 moles, from 0.08 to 1.2 moles, from 0.1 to 1.0 moles, from 0.13 to 0.8 moles per mole of trivalent framework element (e.g. Al) of the zeolite having a CHA-type framework structure. In some particular embodiments wherein copper, iron or a combination thereof is used as the promoter metal, the amount of promoter metal is from 0.1 to 1.0 moles, preferably from 0.15 to 0.8 moles, more preferably from 0.2 to 0.6 moles, most preferably from 0.3 to 0.5 moles per mole of trivalent framework element (e.g. Al) of the zeolite having a CHA-type framework structure.

[0112] In some preferred embodiments, the metal-promoted zeolite having a CHA-type framework structure according to the present application comprises

[0113] - an aluminosilicate zeolite having a CHA-type framework structure having a silica to alumina molar ratio (SAR) in the range of from 10 to 35, and

[0114] - a promoter metal selected from Cu, Fe or a combination thereof, in particular Cu,

[0115] wherein the promoter metal is present in an amount of from 0.2 to 0.6 moles, preferably from 0.3 to 0.5 moles per mole of framework aluminum of the zeolite.

[0116] In some more preferred embodiments, the metal-promoted zeolite having a CHA-type framework structure according to the present application comprises

[0117] - an aluminosilicate zeolite having a CHA-type framework structure having a silica to alumina molar ratio (SAR) of from 15 to 30, more preferably from 18 to 25, and

[0118] - a promoter metal, which promoter metal is Cu,

[0119] wherein Cu is present in an amount of from 0.2 to 0.6 moles per mole of framework aluminum of the zeolite.

[0120] In an exemplary embodiment, the zeolite having a CHA-type framework structure according to the present application comprises - an aluminosilicate zeolite having a CHA-type framework structure having a silica to alumina molar ratio (SAR) of from 18 to 25, and

[0121] - a promoter metal, which promoter metal is Cu,

[0122] wherein Cu is present in an amount of from 0.3 to 0.5 moles per mole of framework aluminum of the zeolite.

[0123] Preferably, the metal-promoted zeolite having a framework structure of CHA type according to the present application can have a NOxconversion of at least 50% at 200°C and at least 60% at 575°C in a test gas stream consisting of 500 vppm NO, 500 vppm NH3, 5 vol% H2O, 10 vol% O2 and the balance N2 at 820°C with 10% H2O steam aging, where the gas hourly space velocity (GHSV) is 120,000 h -1 Preferably, the metal-promoted zeolite having a framework structure of CHA type according to the present application has a NOxconversion of at least 65% at 200°C and at least 75% at 575°C determined under the same conditions as described above. More preferably, the metal-promoted zeolite having a framework structure of CHA type according to the present application has a NOxconversion of at least 70% at 200°C and at least 80% at 575°C determined under the same conditions as described above.

[0124] The promoter metal can be introduced into the zeolite having a framework structure of CHA type via any known method, such as ion exchange and impregnation. For example, the promoter metal can be introduced into the zeolite having a framework structure of CHA type by mixing the zeolite into a solution of a soluble precursor of the promoter metal. After ion exchange of the zeolite with the promoter metal, which is typically in cationic form, the zeolite can be routinely washed, dried and calcined. Useful soluble precursors of the promoter metal can be, for example, salts of the promoter metal, complexes of the promoter metal, and combinations thereof. Alternatively, the promoter metal can be introduced into the zeolite having a framework structure of CHA type in situ during the preparation of a catalytic article, such as an extrudate or a coated monolith, as described below.

[0125] In a fourth aspect, the present application relates to the use of a zeolite having a framework structure of CHA type, obtained or obtainable by the process as described in the first aspect, in a catalyst for the selective catalytic reduction (SCR) of nitrogen oxides. Further, the present application relates to the use of a metal-promoted zeolite having a framework structure of CHA type as described in the third aspect for the selective catalytic reduction (SCR) of NOx.

[0126] For SCR applications, the zeolite having a framework structure of CHA type, preferably a metal-promoted zeolite as described above, can be applied in the form of an extrudate or as a washcoat layer on a monolithic substrate.

[0127] Accordingly, in a fifth aspect, the present application provides a catalytic article in the form of an extrudate comprising a SCR catalyst composition or in the form of a monolith comprising a washcoat layer containing a SCR catalyst composition on a substrate, wherein the SCR catalyst composition comprises a metal-promoted zeolite having a framework structure of CHA type as described in the third aspect.

[0128] The term "extrudate" generally refers to a shaped body formed by extrusion. According to the present application, the extrudate comprising a zeolite having a framework structure of CHA type and a promoter metal generally has a honeycomb structure.

[0129] The term "washcoat" has its usual meaning in the art, i.e. a thin adherent coating of catalytic material or other material applied to a substrate.

[0130] The term "substrate" generally refers to the overall material on which a catalytic coating is disposed, such as a monolithic honeycomb substrate, in particular a flow-through monolithic substrate and a wall-flow monolithic substrate.

[0131] The zeolite having a framework structure of CHA type and the promoter metal can be processed into a catalytic article by any known method without particular restriction.

[0132] In another aspect, the present application relates to an exhaust gas treatment system comprising an internal combustion engine and an exhaust gas conduit in fluid communication with the internal combustion engine, wherein a catalytic article as described herein is present in the exhaust gas conduit.

[0133] In addition thereto, the present application further relates to a process for the selective catalytic reduction of nitrogen oxides, which process comprises contacting a gas stream comprising nitrogen oxides (NOx) with a metal-promoted zeolite comprising a promoter metal as described in the third aspect, or with a catalytic article as described in the fifth aspect.

[0134] The present application is further illustrated by the following set of embodiments and combinations of embodiments resulting from the indicated dependencies and back-references. In particular, it should be noted that in each case where a range of embodiments is mentioned, for example in the context of the term such as "according to any one of embodiments 1 to 4", each one of the embodiments within the range is meant to be explicitly disclosed to the skilled person, i.e. the wording of the term is to be understood by the skilled person as synonymous to "according to any one of embodiments 1, 2, 3 and 4". Furthermore, it is explicitly noted that the following set of embodiments is not a set of claims determining the scope of protection, but rather represents a properly structured part of the description directed to the general and preferred aspects of the present application.

[0135] embodiment

[0136] 1. A process for the preparation of a zeolite having a framework structure of CHA type, the framework structure comprising X2O3 and YO2, wherein X is a trivalent element and Y is a tetravalent element, the process comprising

[0137] (1) preparing a synthesis mixture, the synthesis mixture comprising

[0138] (A) a source of X2O3,

[0139] (B) a source of YO2, and

[0140] (C) a source of an organic structure directing agent (OSDA), the source comprising a bis-quaternary ammonium cation of formula (I) or a combination of bis-quaternary ammonium cations of formula (I),

[0141] (R1R2R3)N + (CH2) n N + (R4R5R6) (I)

[0142] wherein

[0143] R1, R2, R3, R4, R5, and R6 are each independently selected from the group consisting of C1-C6 alkyl, and n is an integer in the range of 3 to 10. 10 alkyl, and the other two are linked together to form a C4-C6 alkylene,

[0144] n is an integer in the range of 3 to 10.

[0145] or

[0146] wherein

[0147] one of R1, R2, and R3 is selected from the group consisting of C1-C6 alkyl, and the other two are linked together to form a C4-C6 alkylene, 10 alkyl, and the other two are linked together to form a C4-C6 alkylene,

[0148] one of R4, R5, and R6 is selected from the group consisting of C1-C6 alkyl, and the other two are linked together to form a C4-C6 alkylene, and 10 alkyl, and the other two are linked together to form a C4-C6 alkylene,

[0149] n is an integer in the range of 3 to 10.

[0150] (2) subjecting the synthesis mixture to crystallization conditions to form a zeolite having a CHA-type framework structure.

[0151] 2. The method according to embodiment 1, wherein in formula (I) R1, R2, R3, R4, R5, and R6 are each independently selected from the group consisting of C1-C6 alkyl, and n is an integer in the range of 3 to 10.

[0152] 3. The method according to embodiment 2, wherein in formula (I) R1, R2, R3, R4, R5, and R6 are the same and selected from the group consisting of C1-C6 alkyl, and n is 4 to 7.

[0153] 4. The method according to embodiment 3, wherein in formula (I) each of R1, R2, R3, R4, R5, and R6 is methyl, ethyl, or propyl, and n is 5, 6, or 7.

[0154] 5. The method according to embodiment 4, wherein in formula (I) each of R1, R2, R3, R4, R5, and R6 is ethyl.

[0155] 6. The method according to embodiment 5, wherein in formula (I) each of R1, R2, R3, R4, R5, and R6 is ethyl and n is 5.

[0156] 7. The method according to any one of embodiments 1 to 6, wherein the synthesis mixture has a molar ratio of the diquaternary ammonium cation to the YO2 source, calculated as YO2, in the range of 0.01 to 1.0, such as 0.05 to 0.5 or 0.08 to 0.2.

[0157] 8. The method according to any one of embodiments 1 to 7, wherein X is selected from the group consisting of Al, B, In, Ga, and any combination thereof, and Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and any combination thereof.

[0158] 9. The method according to embodiment 8, wherein X is Al and Y is Si.

[0159] 10. The method according to any one of embodiments 1 to 9, wherein the X2O3 source and the YO2 source comprise a FAU zeolite, in particular zeolite Y, more preferably zeolite Y having a molar ratio of XO2 to Y2O3 of not more than 40, preferably not more than 30.

[0160] 11. The method according to any one of embodiments 1 to 10, wherein the synthesis mixture has a molar ratio of the YO2 source, calculated as YO2, to the X2O3 source, calculated as X2O3, in the range of 5 to 100, such as 10 to 60 or 15 to 30.

[0161] 12. The method according to any one of embodiments 1 to 11, wherein the synthesis mixture comprises a source of alkali and / or alkaline earth metal cations and has a ratio of the alkali and / or alkaline earth metal cations to the YO2 source, calculated as AM to YO2, in the range of 0.01 to 1.0, such as 0.03 to 0.5 or 0.05 to 0.3.

[0162] 13. The method according to any one of embodiments 1 to 12, wherein the synthesis mixture comprises a source of anionic OH - and has a molar ratio of the anionic OH - to the YO2 source, calculated as OH to YO2, in the range of 0.1 to 2.0, such as 0.1 to 1.0 or 0.2 to 0.5.

[0163] 14. The method according to any one of embodiments 1 to 13, wherein the organic structure directing agent does not comprise a cation other than the bis-quaternary ammonium cation of formula (I).

[0164] 15. A zeolite having a CHA-type framework structure, obtainable and / or obtained by the method according to any one of embodiments 1 to 14.

[0165] 16. The zeolite according to embodiment 15, having a YO2:X2O3 molar ratio of 2 or more, preferably in the range of 4 to 200, more preferably 6 to 100, more preferably 8 to 50, more preferably 10 to 35, more preferably 15 to 30, most preferably 18 to 25.

[0166] 17. The zeolite according to embodiment 15 or 16, having a crystal morphology with a crystal surface having a tessellation pattern texture, as observed via SEM.

[0167] 18. A metal-promoted zeolite having a CHA-type framework structure, comprising the zeolite according to any one of embodiments 15 to 17 and a promoter metal.

[0168] 19. The metal-promoted zeolite according to embodiment 18, wherein the promoter metal is selected from the group consisting of transition metals, alkaline earth metals, Sb, Sn and Bi and any combination thereof, preferably comprising Cu and / or Fe, preferably Cu.

[0169] 20. The metal-promoted zeolite according to embodiment 19, wherein the promoter metal consists of Cu and / or Fe, preferably Cu.

[0170] 21. The metal-promoted zeolite according to embodiment 20, wherein the promoter metal is present in the metal-promoted zeolite in an amount in the range of 0.1 mole to 1.0 mole, preferably 0.15 mole to 0.8 mole, more preferably 0.2 mole to 0.6 mole, most preferably 0.3 mole to 0.5 mole.

[0171] 22. The metal-promoted zeolite according to any one of embodiments 18 to 21, having a NOx conversion of at least 50% at 200°C and at least 60% at 575°C in a test gas stream consisting of 500 vppm NO, 500 vppm NH3, 5 vol% H2O, 10 vol% O2 and the balance N2, when aged with 10% H2O steam at 820°C, wherein the gas hourly space velocity (GHSV) is 120,000 h -1 .

[0172] 23. The metal-promoted zeolite according to embodiment 22, having a NOxconversion of at least 65% at 200°C and at least 75% at 575°C, preferably at least 70% at 200°C and at least 80% at 575°C, when aged with 10% H2O steam at 820°C.

[0173] 24. A catalytic article in the form of an extrudate comprising an SCR catalyst composition or in the form of a monolith comprising a washcoat comprising an SCR catalyst composition on a substrate, wherein the SCR catalyst composition comprises the metal-promoted zeolite according to any one of embodiments 18 to 23.

[0174] 25. An exhaust gas treatment system comprising an internal combustion engine and an exhaust gas conduit in fluid communication with the internal combustion engine, wherein the catalytic article according to embodiment 24 is present in the exhaust gas conduit.

[0175] 26. Use of the zeolite having a CHA-type framework structure according to any one of embodiments 15 to 17 or the metal-promoted zeolite according to any one of embodiments 18 to 23 in a catalyst for the selective catalytic reduction of nitrogen oxides.

[0176] 27. A method for the selective catalytic reduction of nitrogen oxides, the method comprising contacting a gas stream comprising nitrogen oxides (NOx) with the metal-promoted zeolite according to any one of embodiments 18 to 23 or the catalytic article according to embodiment 24.

[0177] The present application will be further illustrated by the following examples, which set forth particularly advantageous embodiments. Although the examples are provided to illustrate the present application, they are not intended to limit the application.

[0178] example

[0179] Scanning electron microscopy (SEM) measurements were performed by scanning electron microscopy (Hitachi SU5000).

[0180] X-ray powder diffraction (XRD) patterns were measured with a PANalytical X'pert 3 Proteus powder diffractometer (40 kV, 40 mA) using Cu K-alpha Data were collected in Bragg-Brentano geometry.

[0181] Example 1 Preparation of seeds of CHA zeolite

[0182] A solution of 814.6 g 1 -methyl- 1 -n-propylpiperidinium hydroxide (12.6 wt%) in water was mixed with 2814.3 g deionized water, followed by the addition of 110.8 g sodium hydroxide (99%, solid). After the sodium hydroxide was dissolved, 44.9 g zeolite HY (SAR = 7.2, from Shandong Duoyou) and 567.6 g AS-40 colloidal silica. After stirring for 30 minutes at room temperature, the synthesis mixture was transferred to a Teflon-lined autoclave for crystallization. Crystallization was carried out at 150 °C for 5 days under static conditions. After cooling to room temperature, the zeolite product was collected by filtration and dried at 120 °C overnight.

[0183] The as-synthesized zeolite was calcined at 550 °C for 6 hours to remove the organic structure directing agent. The calcined zeolite was crushed and ion exchanged in 10 wt% aqueous NH4C1 solution at a solid to liquid ratio of 1 : 10. The ion exchange process was carried out at 80 °C for 2 hours, collected by filtration, washed with deionized water, and dried at 110 °C overnight. The ion exchange process was repeated once and the dried product was calcined at 450 °C for 6 hours to obtain the calcined H-form zeolite.

[0184] The zeolite had a Si02 / A1203 molar ratio (SAR) of 14.2 as measured on the calcined H-form by XRF. The zeolite was confirmed to have a typical CHA-type framework by the XRD pattern.

[0185] Example 2 Preparation of CHA zeolite (Zeolite A, calcined H form) with N,N,N,N',N',N'-hexaethyl-1,5-pentanediammonium dihydroxide (Et6-diquat-5 dihydroxide) Figure 1A

[0186] A solution of 814.6 g 1 -methyl- 1 -n-propylpiperidinium hydroxide (12.6 wt%) in water was mixed with 2814.3 g deionized water, followed by the addition of 110.8 g sodium hydroxide (99%, solid). After the sodium hydroxide was dissolved, 44.9 g zeolite HY (SAR = 7.2, from Shandong Duoyou) and 567.6 g

[0187] The as-synthesized zeolite was calcined at 550 °C for 6 hours to remove the organic structure directing agent. The calcined zeolite was crushed and ion exchanged in 10 wt% aqueous NH4C1 solution at a solid to liquid ratio of 1 : 10. The ion exchange process was carried out at 80 °C for 2 hours, collected by filtration, washed with deionized water, and dried at 110 °C overnight. The ion exchange process was repeated once and the dried product was calcined at 450 °C for 6 hours to obtain the calcined H-form zeolite.

[0188] The zeolite has a Si02 / A1203 molar ratio (SAR) of 22 as measured by XRF on the calcined H-form.

[0189] The crystal morphology of the zeolite as observed from SEM images (at 15.0 KV, 6.1 mm x 30.0 K) and XRD pattern of the zeolite are shown in Figure 2 and Example 3 Preparation of CHA zeolite (Zeolite B, calcined H form) with N,N,N,N',N',N'-hexaethyl-1,5-pentanediammonium dihydroxide (Et6-diquat-5 dihydroxide) respectively. The zeolite was confirmed to have a typical CHA-type framework by the XRD pattern. In addition, the tessellation pattern texture on the surface of the zeolite crystals was clearly observed from the SEM photograph.

[0190] Figure 1B Figure 2

[0191] An aqueous solution of 173.4 g Et6-diquat-5 dihydroxide (20 wt%) was mixed with 208.3 g of deionized water, followed by the addition of 7.1 g of sodium hydroxide (99%, solid). After the sodium hydroxide was dissolved, 35.8 g of zeolite HY (SAR = 7.2, from Shandong Duoyou) and 114.3 g of AS-40 colloidal silica were added. After stirring for 30 minutes at room temperature, 2.4 g of CHA seeds were added and the synthesis mixture was transferred to a Teflon lined autoclave for crystallization. Crystallization was carried out at 180 °C under static conditions for 2 days. After cooling to room temperature, the zeolite product was collected by filtration and dried at 120 °C overnight.

[0192] The as-synthesized zeolite was calcined at 550 °C for 6 hours to remove the organic structure directing agent. The calcined zeolite was crushed and ion exchanged in a 10 wt% aqueous NH4C1 solution at a solid to liquid ratio of 1 : 10. The ion exchange process was carried out at 80 °C for 2 hours, collected by filtration, washed with deionized water, and dried at 110 °C overnight. The ion exchange process was repeated once and the dried product was calcined at 450 °C for 6 hours to obtain the calcined H-form zeolite.

[0193] The zeolite has a Si02 / A1203 molar ratio (SAR) of 20 as measured by XRF on the calcined H-form.

[0194] The crystal morphology of the zeolite as observed from SEM images (at 15.0 KV, 8.2 mm x 50.0 K) and XRD pattern of the zeolite are shown in Example 4 Preparation of CHA zeolite (Zeolite C, calcined H form) with N,N,N-trimethyl-1 -adamantylammonium hydroxide and Figure 1C respectively. The zeolite was confirmed to have a typical CHA-type framework by the XRD pattern. In addition, the tessellation pattern texture on the surface of the zeolite crystals was clearly observed from the SEM photograph.

[0195] Figure 2

[0196] To a solution of 0.5 g sodium hydroxide (99%, solid) in 35 g deionized water was added 95 g sodium silicate, 3 g sodium sulfate (99%, solid), followed by 9 g zeolite Na-Y (SAR = 5.1, CBV 100 from Zeolyst). Then, 16 g of an aqueous solution of N,N,N-trimethyl-1- adamantylammonium hydroxide (TMAdaOH, 20 wt%) was added and stirred at room temperature for 30 minutes. The synthesis mixture was then transferred to a Teflon lined autoclave for crystallization. Crystallization was carried out at 140 °C for 3 days under static conditions. After cooling to room temperature, the zeolite product was collected by filtration and dried at 120 °C overnight.

[0197] The as-synthesized zeolite was calcined at 550 °C for 6 hours to remove the organic structure directing agent. The calcined zeolite was pulverized and ion exchanged in 10 wt% aqueous NH4C1 solution at a solid to liquid ratio of 1:10. The ion exchange process was carried out at 80 °C for 2 hours, collected by filtration, washed with deionized water, and dried at 110 °C overnight. The ion exchange process was repeated once and the dried product was calcined at 450 °C for 6 hours to obtain the calcined H-form zeolite.

[0198] The zeolite had a Si02 / Al203mole ratio (SAR) of 11 as measured on the calcined H-form by XRF.

[0199] The crystal morphology of the zeolite observed from the SEM image (at 15.0 KV, 5.3 mm x 5.00K) and XRD pattern of the zeolite are shown in Example 5 Preparation of Cu-loaded CHA zeolite material (SCR catalyst) and Table 2 respectively. The zeolite was confirmed to have a typical CHA-type framework by the XRD pattern. However, no mosaic pattern texture on the surface of the zeolite crystals was observed from the SEM photograph.

[0200] Example 6 Testing of catalyst performance

[0201] The obtained calcined H-form zeolite powder was impregnated with an aqueous copper (II) nitrate solution by incipient wetness impregnation and kept in a sealed container at 50 °C for 20 hours. The obtained solid was dried and calcined in a furnace in air at 450 °C for 5 hours to obtain a Cu-promoted CHA zeolite.

[0202] The Cu-promoted CHA zeolites prepared according to the general procedure described above are summarized in Table 2 below.

[0203] Table 3

[0204]

[0205] ​

[0206] To test SCR performance, each of the Cu-loaded zeolitic materials was slurried with an aqueous solution of zirconium acetate, then dried at ambient temperature under air with stirring, and calcined at 550 °C for 1 hour to provide a product containing 5 wt% Zr02as binder based on the amount of product. The product was crushed and the 250-500 micron powder fraction was aged in a 10 vol% steam / air stream at 650 °C for 50 hours or at 820 °C for 16 hours to provide samples for testing.

[0207] Selective Catalytic Reduction (SCR) tests were performed in a fixed bed reactor according to the following conditions, wherein 80 mg of test sample was loaded with corundum of the same sieve fraction as diluent to about 1 mL bed volume:

[0208] Gas feed: 500 vppm NO, 500 vppm NH3, 5 vol% H20, 10 vol% 02and balance N2, with a gas hourly space velocity (GHSV) of 120,000 h -1 ;

[0209] Temperature: Run 1 - 200 °C, 400 °C, 575 °C (first run for slight aging)

[0210] Run 2 - 175 °C, 200 °C, 225 °C, 250 °C, 500 °C, 550 °C, 575 °C.

[0211] The NOxconversion rates measured at 200 °C and 575 °C from Run 2 are reported as test results, which are summarized in Table 3 below.

[0212] ​

[0213]

[0214] It can be seen that the catalysts comprising Cu-promoted CHA zeolites according to the present application are effective for the selective catalytic reduction (SCR) of nitrogen oxides.

[0215] Surprisingly, the inventive catalyst A.2 (Example 2) based on CHA zeolite A prepared with a double-quaternary ammonium cation OSDA has a higher NOxconversion rate when aged at 650 °C compared to comparative catalyst D.1 (Example 4) based on CHA zeolite D prepared at the same Cu / Al ratio but using the conventional TMAdaOH OSDA.

[0216] Furthermore, the inventive catalysts A.1 to A.4 have a much improved NOx conversion at aging at 820 °C compared to the comparative catalyst D.1. The inventive catalysts have a NOx conversion at 200 °C of more than 70 %, even up to 79 %, and a NOx conversion at 575 °C of more than 80 %, even up to 91 % at aging at 820 °C, whereas in case of the respective comparative catalysts the NOx conversion is "0". The relatively high SCR activity of the inventive catalysts after aging at 820 °C reflects the high stability of the CHA zeolite at very high temperatures.

[0217] While the application has been described herein with reference to particular embodiments thereof, a latitude of modification, various changes and substitutions are intended in the foregoing disclosures, and in some instances some features of the present application will be employed without a corresponding use of other features. It will be appreciated that in some embodiments, the application can include any of the features set forth herein, alone or in any combination thereof. Accordingly, any one or more features can be included in, or omitted from, any disclosed embodiment without changing the essence of the application.

Claims

1. A method for preparing a zeolite having a CHA-type framework structure comprising X2O3 and YO2, wherein X is a trivalent element and Y is a tetravalent element, the method comprising (1) preparing a synthetic mixture, the synthetic mixture comprising (A) X2O3 source, (B) YO2 sources, and (C) a source of an organic structure directing agent (OSDA), said source comprising a diquaternary ammonium cation of formula (I) or a combination of diquaternary ammonium cations of formula (I), (R1R2R3)N + (CH2) n N + (R4R5R6)(I) in R1, R2, R3, R4, R5 and R6 are independently selected from C1-C 10 alkyl, and n is an integer ranging from 3 to 10, or in One of R1, R2 and R3 is selected from C1-C 10 alkyl, and the other two are linked together to form a C4-C6 alkylene group, One of R4, R5 and R6 is selected from C1-C 10 alkyl, and the other two are linked together to form a C4-C6 alkylene, and n is an integer in the range of 3 to 10; and (2) Subjecting the synthesis mixture to crystallization conditions to form a zeolite having a CHA-type framework structure.

2. The method according to claim 1, wherein in formula (I), R1, R2, R3, R4, R5 and R6 are independently selected from C1-C6 alkyl groups, and n is an integer in the range of 3 to 10.

3. The method according to claim 2, wherein in formula (I), R1, R2, R3, R4, R5 and R6 are the same and are selected from C1-C6 alkyl, and n is 4 to 7.

4. The method according to claim 3, wherein in formula (I), each of R1, R2, R3, R4, R5 and R6 is methyl, ethyl or propyl, preferably ethyl, and n is 5, 6 or 7. 5 . The method according to claim 4 , wherein in formula (I), each of R 1 , R 2 , R 3 , R 4 , R 5 and R 6 is an ethyl group and n is 5.

6. The method according to any one of claims 1 to 5, wherein the synthesis mixture has a molar ratio of the diquaternary ammonium cation to the source of YO2 calculated as YO2 in the range of 0.01 to 1.0, such as 0.05 to 0.5 or 0.08 to 0.

2.

7. The method according to any one of claims 1 to 6, wherein X is selected from the group consisting of Al, B, In, Ga, and any combination thereof, and Y is selected from the group consisting of Si, Sn, Ti, Zr, Ge, and any combination thereof. The method of claim 7 , wherein X is Al and Y is Si.

9. The process according to any one of claims 1 to 8, wherein the X2O3 source and the YO2 source comprise FAU zeolites, in particular zeolite Y, more preferably zeolite Y having a molar ratio of XO2 to Y2O3 of not more than 40, preferably not more than 30.

10. The method according to any one of claims 1 to 9, wherein the synthesis mixture has a molar ratio of the source of YO2 calculated as YO2 to the source of X2O3 calculated as X2O3 in the range of 5 to 100, such as 10 to 60 or 15 to 30.

11. A method according to any one of claims 1 to 10, wherein the synthesis mixture comprises a source of alkali metal and / or alkaline earth metal cations and has a ratio of the alkali metal and / or alkaline earth metal cations to the source of YO2 calculated as AM to YO2 in the range of 0.01 to 1.0, such as 0.03 to 0.5 or 0.05 to 0.

3.

12. The method according to any one of claims 1 to 11, wherein the synthesis mixture comprises anions OH - source, and having a OH content in the range of 0.1 to 2.0, e.g., 0.1 to 1.0 or 0.2 to 0.5 - The anion OH calculated by YO2 - The molar ratio of YO2 to the source.

13. The method of any one of claims 1 to 12, wherein the organic structure directing agent does not comprise a cation other than the diquaternary ammonium cation of formula (I).

14. A zeolite having a CHA-type framework structure, the zeolite being obtainable and / or obtainable by the method according to any one of claims 1 to 13.

15. The zeolite according to claim 14, having a YO2:X2O3 molar ratio of 2 or more, preferably in the range of 4 to 200, more preferably 6 to 100, more preferably 8 to 50, more preferably 10 to 35, more preferably 15 to 30, most preferably 18 to 25.

16. The zeolite according to claim 14 or 15, having a crystal morphology with a mosaic pattern texture on the crystal surface, as observed via SEM. 17 . A metal-promoted zeolite having a CHA-type framework structure, comprising the zeolite according to claim 14 and a promoter metal.

18. The metal-promoted zeolite according to claim 17, wherein the promoter metal is selected from transition metals, alkaline earth metals, Sb, Sn and Bi and any combination thereof, preferably comprising Cu and / or Fe, preferably Cu.

19. The metal-promoted zeolite according to claim 17 or 18, wherein the promoter metal consists of Cu and / or Fe, preferably consists of Cu.

20. The metal-promoted zeolite of claim 19, wherein the promoter metal is present in the metal-promoted zeolite in an amount ranging from 0.1 to 1.0 moles, preferably from 0.15 to 0.8 moles, more preferably from 0.2 to 0.6 moles, most preferably from 0.3 to 0.5 moles.

21. The metal-promoted zeolite of any one of claims 17 to 20, having a NOx conversion of at least 50% at 200°C and at least 60% at 575°C when aged with 10% H2O steam at 820°C in a test gas stream consisting of 500 vppm NO, 500 vppm NH3, 5 vol% H2O, 10 vol% O2, and the balance N2, with a gas hourly space velocity (GHSV) of 120,000 h -1 .

22. The metal-promoted zeolite of claim 21 having a NOx conversion of at least 65% at 200°C and at least 75% at 575°C, preferably at least 70% at 200°C and at least 80% at 575°C when aged with 10% H2O steam at 820°C.

23. A catalytic article in the form of an extrudate or a monolith comprising a washcoat containing an SCR catalyst composition on a substrate, wherein the SCR catalyst composition comprises the metal-promoted zeolite according to any one of claims 17 to 22.

24. An exhaust treatment system comprising an internal combustion engine and an exhaust conduit in fluid communication with the internal combustion engine, wherein the catalytic article of claim 23 is present in the exhaust conduit.

25. Use of the zeolite having a CHA-type framework structure according to any one of claims 14 to 16 or the metal-promoted zeolite according to any one of claims 17 to 22 in a catalyst for the selective catalytic reduction of nitrogen oxides.

26. A process for the selective catalytic reduction of nitrogen oxides, the process comprising contacting a gas stream comprising nitrogen oxides (NOx) with the metal-promoted zeolite of any one of claims 17 to 22 or the catalytic article of claim 23.

Citation Information

Patent Citations

  • Method for preparing CHA-type molecular sieves using novel structure directing agents

    US20100254895A1

  • Zeolite SSZ-13 and its method of preparation

    US4544538A

  • Synthesis of zeolitic materials using n,n-dimethyl organotemplates

    WO2013035054A1

  • Method for the preparation of a molecular sieve of the CHA-type

    WO2020039074A1